Digital scholarship tra ricerca e didattica Studi, ricerche, esperienze - FEDERIGHI, PAOLO; Ranieri, Maria; Bandini, Gianfranco (Media e tecnologie per la didattica - Open Access, 2019)
This volume collects the contributions presented at the conference "Digital scholarship between research and teaching. Studies, research, experiences "(Florence, 5 October 2017), which involved national and international experts in a common reflection on the cultural, political and educational implications of the digitization processes of the Scholarship and, more generally, of university life.